Rebel music : resistance through hip hop and punk - Parmar, Priya; Nocella, Anthony J., II; Robertson, Scott; Diaz, Martha (Emerald Publishing Limited : Information Age Publishing, 2015)
Arising from the street corners and underground clubs, Rebel Music: Resistance through Hip Hop and Punk, challenges standardized schooling and argues for equity, peace, and justice. Rebel Music is an important, one-of-a-kind book that takes readers through fun, radical, educational chapters examining Hip Hop and Punk songs, with each section addressing a particular social issue. Rebel Music values the experiences found in both movements as cultural capital that is de-valued in the current oppressive, standard, test-driven, rule-bound, and corporate schooling experience, making youth "just another brick in the wall." This collection is a "rebel yell" to administrators, teachers, parents, police, politicians, and counselors who demonize Hip Hop and Punk to listen up and respect youth culture. Finally, Rebel Music is a celebration of radical voices and an organizing tool for those who use music to challenge oppression.
Keywords: Rap (Music) -- Social aspects.; Punk rock music -- Social aspects.; Rap (Music) -- History and criticism.; Punk rock music -- History and criticism.; Youth -- Attitudes.; Music -- History & Criticism.; Popular music.; History of music.; Music reviews and criticism.; elektronické knihy; electronic books